Pengaruh Budaya Organisasi Terhadap Kinerja Instansi Pemerintah Dengan Kapasitas Manajemen Kewirausahaan Sebagai Variabel Intervening - Rizki Ramadentinata; Lili Anita (Wahana Riset Akuntansi, 2013)
This study aims to determine: 1) Effect of Organizational Culture on Performance of Local Government Agencies, 2) Effect of Entrepreneurial Management Capacity of the Local Government Performance, 3) Effect of Organizational Culture on Government Performance Management Capacity Region with Entrepreneurship as an intervening variable. Type of research is causative. The population in this study is SKPD in Padang. The total sample taking technique of sampling. Data analysis using path analysis. The results show that: (1) organizational culture have a significant positive impact on the performance of local government (2) Capacity entrepreneurial management had no significant negative effect on the performance of local government agencies. (3) organizational culture had no significant negative effect on the performance of local government through entrepreneurial management capacity Keywords: Organizational Culture, Local Government Performance and Capacity Management Entrepreneurship.